Ultrasound-induced modifications of Auricularia auricula polysaccharides: Implications for antioxidant and glucose-lowering activities - Te Yu; Yonggang Dai; Zifei Wang; Yang Gao; Qiong Wu (Food Chemistry: X)
High molecular mass and poor solubility of Auricularia auricula polysaccharides (AAP) limit their physiological activity. This study employed ultrasonic degradation to address these challenges. Ultrasonic treatment reduced the molecular mass of AAP from 1 × 105 Da to 3.8 × 103–8 × 104 Da, enhanced hydroxyl group exposure, and significantly improved solubility, with dissolution time reduced to one-ninth of the pre-degradation level at 20 °C. The antioxidant activities of AAP were enhanced after ultrasonic degradation, with DPPH scavenging IC50 reduced from 3.58 mg/mL to 2.07 mg/mL and hydroxyl radical IC50 from 2.28 mg/mL to 1.77 mg/mL. Hypoglycemic effects were improved, with α-amylase and α-glucosidase inhibition rates increasing by 5.06 % and 5.81 %, respectively. Bile acid binding for MBS improved by 28.6 %, indicating ultrasonic degradation enhanced hypolipidemic activity. This study demonstrates ultrasonic degradation is a green, efficient method to improve AAP's functional properties, which broadens its applications in functional foods and health supplements.